2003
DOI: 10.1210/jc.2002-021942
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Soluble Vascular Endothelial Growth Factor Receptor 1 (sVEGFR-1) Levels in Women with Preeclampsia

Abstract: Hoping to get more insight into a role of vascular endothelial growth factor (VEGF), a putative substance involved in the development of preeclampsia, we measured concentrations of soluble VEGF receptor-1 (sVEGFR-1), a natural antagonist of VEGF, in serum from women with (n = 31) and without (n = 52) preeclampsia. The concentrations of sVEGFR-1 in serum from women with preeclampsia (median 7791 pg/mL) were > 6-fold higher than those from control (1132 pg/mL, p < 0.0001). The levels of sVEGFR-1 decreased marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
202
2
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(224 citation statements)
references
References 0 publications
9
202
2
11
Order By: Relevance
“…[16][17][18] Moreover, recent reports have indicated that the soluble form of the VEGF receptor-1 (sFlt-1) is increased in the placenta and serum of women with PE. [18][19][20][21] Thus, sFlt-1 may act by sequestering free PlGF and free VEGF, thereby preventing interaction between endothelial Median (interquartile range).…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Moreover, recent reports have indicated that the soluble form of the VEGF receptor-1 (sFlt-1) is increased in the placenta and serum of women with PE. [18][19][20][21] Thus, sFlt-1 may act by sequestering free PlGF and free VEGF, thereby preventing interaction between endothelial Median (interquartile range).…”
Section: Discussionmentioning
confidence: 99%
“…Excess sFlt1 alone, when administered to pregnant rats, induces albuminuria, hypertension, and renal pathologic changes of glomerular endotheliosis by antagonizing circulating VEGF and PlGF and inducing endothelial dysfunction. In addition, circulating levels of free VEGF and free PlGF were decreased in conjunction with elevated sFlt1 in the bloodstream at the time of disease presentation (39,40). More recently, when free PlGF and free VEGF were measured throughout pregnancy, the growth factors were decreased in preeclamptic women well before the onset of clinical disease (46 -48).…”
Section: Circulating Proangiogenic Factors and Their Inhibitorsmentioning
confidence: 99%
“…It seems that during pregnancy most of the circulating VEGF is bound to sVEGFR-1 produced in high amounts by the placenta [19][20][21]. In preeclampsia, placental production of VEGFR-1 and sVEGFR-1 is likely increased because of low oxygen levels in the placenta.…”
Section: Expression Of Vegf Plgf and Their Receptors In Pregnancies mentioning
confidence: 99%